The immunocytochemical localization of potential Z-DNA sites in human testicular tubule epithelium - Jagiello, G. M. (Biology of reproduction, 1988)
Z-DNA has been detected in several pro- and eukaryotic cells and possible roles in regulating transcriptional activity and meiotic recombination proposed. The present study examined the localization of reaction product to potential Z-DNA sites in human testicular tubule epithelium from three subjects using an avidin-biotin complex (ABC)-immunoperoxidase method with a specific rabbit antibody previously shown to react with rat spermatogonial nuclei. A total of 46,626 cells were scored, of which 5656 were Sertoli cells. Eighty-six percent of spermatogonia in mitotic metaphase were found to be negative. Interphase spermatogonia identified as A dark or pale were positive in 93 and 92%, respectively, of cells, and this positivity persisted through B spermatogonia into meiosis. Of 8083 leptotene/zygotene spermatocytes, 99% were positive. Pachytene spermatocytes were 98% positive in the autosomal bivalents. First meiotic metaphase nuclei were negative (92%), as were almost all cells scored of the spermiogenic series (16,195). Nuclei of Sertoli cells had reaction product over the chromatin in 81% of 5656 cells, with no reaction product on the prominent nucleolus. The presence of potential Z-DNA sites in the genome of human spermatogenesis and Sertoli cells during known active stages of transcription (pachytene) and recombination (zygotene/pachytene) suggests a role for this conformation during these stages.